2019
DOI: 10.1186/s40834-019-0089-x
|View full text |Cite
|
Sign up to set email alerts
|

Cystoscopic removal of a migrated intrauterine device to the bladder; a case report

Abstract: Background An intrauterine device (IUD) is a well-accepted means of reversible contraception. Migration of IUD to the bladder through partial or complete perforation has been rarely reported. This phenomenon could be strongly associated with history of prior cesarean sections (C-section) or early insertion of the device in the postpartum period. Case presentation In this study, a case of copper IUD migration through cesarean scar defect is presented, in such a way that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The removal of the fully migrated IUD from the bladder is most often performed during cystoscopy [13], without difficulty in the cases seen early as in our case. In some cases, the removal is preceded by lithotripsy in the case of a calcified IUD.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The removal of the fully migrated IUD from the bladder is most often performed during cystoscopy [13], without difficulty in the cases seen early as in our case. In some cases, the removal is preceded by lithotripsy in the case of a calcified IUD.…”
Section: Discussionmentioning
confidence: 80%
“…However, cystoscopy remains essential for a complete evaluation of the bladder. It may reveal the presence or absence of a foreign body such as calculus and also help in determining if the migration is partial or complete into the bladder [13]. A blue methylene test or cystography is often useful to rule out fistula.…”
Section: Discussionmentioning
confidence: 99%
“…A similar case reported by Vahdat et al noted that no stones were found in the bladder from an IUCD that had migrated there and been present for five years. However, there was a risk factor from previous scar defects that occurred, which resulted in bladder perforation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…When an IUCD becomes displaced or migrates, it can lead to severe complications such as bowel perforation, hydronephrosis, and even renal failure. The occurrence of an IUCD translocating into the bladder is an uncommon event that may be linked to the lower urinary tract symptoms, formation of vesicouterine fistula, development of bladder stones, or bladder perforation [ 5 ]. Endoscopic treatments and open surgical removal are two therapeutic options for an intrauterine device in the bladder [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…All migrated Cu-IUCDs require removal, which can be achieved by different routes. Most of the intravesical Cu-IUCDs can be managed endoscopically [9][10]. Cystoscopy helps in planning the optimal management and must be performed before embarking on removal.…”
Section: Case Presentationmentioning
confidence: 99%